2018
DOI: 10.1002/cpe.4773
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and analysis of the performance of exascale photonic networks

Abstract: Photonics technology has become a promising and viable alternative for both on-chip and off-chip interconnection networks of future Exascale systems. Nevertheless, this technology is not mature enough yet in this context, so research efforts focusing on photonic networks are still required to achieve realistic suitable network implementations. In this regard, system-level photonic network simulators can help guide designers to assess the multiple design choices. Most current research is done on electrical netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…This aggregated bandwidth is distributed among several channels, and each channel is used for a different transmission. A previous study [8] found that five 320-Gbps channels provide the best performance for an aggregated link bandwidth of 1.6 Tbps. Henceforth, this will be the number of channels assumed in this work.…”
Section: ) Circuit Switchingmentioning
confidence: 96%
See 1 more Smart Citation
“…This aggregated bandwidth is distributed among several channels, and each channel is used for a different transmission. A previous study [8] found that five 320-Gbps channels provide the best performance for an aggregated link bandwidth of 1.6 Tbps. Henceforth, this will be the number of channels assumed in this work.…”
Section: ) Circuit Switchingmentioning
confidence: 96%
“…Note, that if pure circuit switching is used then network resources are blocked for a longer time, which causes this switching technique to present a poor utilization of the network resources mainly due to the high number of reservation conflicts. We identified this problem in a previous work [8], where we showed that photonics can provide important performance improvements when applied to conventional topologies like torus and fat tree networks. Nevertheless, we found that photonic links were underused, which indicates that there is a high potential to improve performance.…”
Section: Introductionmentioning
confidence: 99%
“…Also focused on the interconnection network of an exascale system, Duro et al conduct an extensive simulation study using realistic photonic network configurations with synthetic and realistic traffic and show that, compared to electrical networks, optical networks can reduce the execution time of the studied real workloads in almost one order of magnitude. The study is performed from an architectural perspective, and the authors state that the photonic configuration highly impacts on the network performance, being the bandwidth per channel and the message length the most important parameters.…”
Section: Summary Of Contributionsmentioning
confidence: 99%